The Role of Parents Discipline Early Childhood in Using the Internet as a Learning Media - Teresia Wanda; Enceng Mulyana (IKIP Siliwangi Bandung, 2019)
Instilling discipline in early childhood is not an easy thing to do, in daily practice requires perseverance, patience, exemplary, and of course love. Parents in this case play a very important role in laying the foundation of children's behavior to make children an investment in the future where children are equipped with good character and education so that they are ready to face the global community and the world so they can adapt to the environment they face later, and implement disciplinary attitudes in early childhood to cultivate character.In this study the researchers focused on the application of early childhood kindergarten Yos Sudarso Bandung in using the internet as a medium of learning conducted at home in the supervision and guidance of parents which became the basis and reason in reviewing the problems of the research findings.Based on the results of the study, the following data are obtained: 1) Planning carried out before instilling a discipline pattern is by identifying the extent to which parents provide freedom and guidance to early age children in using the internet at home as learning needs and providing learning motivation as a first step in preparing mental age children early in following the application of discipline. 2) Implementation of discipline implementation is carried out in daily habituation programs. The method used is a time playing internet program for children through parental guidance. The approach taken is by guiding, paying attention and watching over children in using internet social media to be a positive source of learning and generate creativity and imaginative in children. 3) Evaluation of this discipline planting pattern is focused on the cultivation of discipline, disciplinary processes and results so that the implementation of disilplin has not been able to run optimally due to the inhibiting factors that must be addressed. Keywords: Discipline and family education.